2015
DOI: 10.2147/dmso.s85318
|View full text |Cite
|
Sign up to set email alerts
|

Red cell distribution width in type 2 diabetic patients

Abstract: ObjectiveTo study the indices of some elements of the complete blood count, in type 2 diabetic patients, in comparison with nondiabetic healthy controls; and to find out the effects of glycemic control and different medications on these indices. To the best of our knowledge, this study is novel in our environment and will serve as a foundation for other researchers in this field.MethodsThis retrospective study included 260 type 2 diabetic patients on treatment and 44 healthy control subjects. Sex, age, weight,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
72
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 41 publications
7
72
3
2
Order By: Relevance
“…MPV, PDW, or PCT values were not different between groups, similar to Nada [21]'s study, which observed that diabetic patients receiving aspirin or clopidogrel did not show significant differences in MPV when compared with controls [19]. Hyperglycaemia may decrease the effectiveness of antiplatelet therapy by increasing reactive oxidant species and lead to aspirin resistance by binding to thromboxane receptors, whereas hypercholesterolaemia may blunt aspirin's effect on thrombin [23,24].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…MPV, PDW, or PCT values were not different between groups, similar to Nada [21]'s study, which observed that diabetic patients receiving aspirin or clopidogrel did not show significant differences in MPV when compared with controls [19]. Hyperglycaemia may decrease the effectiveness of antiplatelet therapy by increasing reactive oxidant species and lead to aspirin resistance by binding to thromboxane receptors, whereas hypercholesterolaemia may blunt aspirin's effect on thrombin [23,24].…”
Section: Discussionsupporting
confidence: 81%
“…Aspirin's effect on platelet aggregation is subject to inter-individual and intra-individual variability, which can be attributed to multifactorial reasons [20][21][22]. MPV, PDW, or PCT values were not different between groups, similar to Nada [21]'s study, which observed that diabetic patients receiving aspirin or clopidogrel did not show significant differences in MPV when compared with controls [19].…”
Section: Discussionmentioning
confidence: 51%
“…They discovered RDW was returned to normal after plasma glucose levels and metabolic acidosis were controlled. In a similar study conducted in 2015, it was reported that patients with diabetes had distinctively higher values of RDW compared with healthy individuals, and anisocytosis developed due to impaired erythropoiesis, agglutination, or eryth- rocyte degranulation with fragmentation [15]. Conversely, we found no difference in the RDW, MCV, and RDW/MCV values between groups in our study (p<0.05).…”
Section: Discussioncontrasting
confidence: 56%
“…According to the available results, we didn't determine a statistically significant correlation between HbA1C and RDW in the control group, case group or in total.But hyperglycemia has several effects on red blood cells (RBC)s, besides formation of HbA1C. It leads to change in erythrocyte structure, hemodynamic parametres, increased osmotic fragility and also reduces RBC life span [20]. In studies made with much more patients, a close relation was found between RDW and HbA1C, the reason that we couldn't find such a relation may be the low number of patients in the groups and more extensive studies with more patients are needed on this subject.…”
Section: Discussionmentioning
confidence: 99%